(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The article presents and criticizes the ruling n. 84/2016 of the Italian Con-stitutional Court on the research on “left over” human embryos. In particular, the au-thor focuses on the risk that the approach of the Court will lead “ethically sensitive” issues outside the scope of judicial review of legislation.